2005
DOI: 10.1038/sj.bjp.0706357
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic innervation of the mouse isolated vas deferens

Abstract: 1 Recently, a population of nerves has been described in the aganglionic mouse vas deferens, in which electrically evoked contractions were insensitive to high concentrations of the adrenergic neurone blocker, bretylium. In this paper, the pharmacology of this nerve-evoked contraction has been examined in more detail. 2 Bretylium (20 mM) revealed, after 5 h exposure, a new residual neurogenic contraction (20 stimuli at 10 Hz) that was tetrodotoxin-sensitive. 3 The muscarinic antagonist, cyclopentolate (0.1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…Acetylcholine has also been shown to enhance noradrenalinemediated contraction in the human prostate (Roosen et al, 2009), indicating a possible synergism. It has been shown that there are functional muscarinic receptors mediating contraction in vasa deferentia taken from the mouse (Cuprian et al, 2005) and guinea pig (Solanki et al, 2007), and we also observed that atropine attenuated contraction in vasa deferentia taken from wild-type mice. However, after purinergic and adrenergic blockade we did not observe a cholinergic residual response.…”
Section: Discussionsupporting
confidence: 74%
“…Acetylcholine has also been shown to enhance noradrenalinemediated contraction in the human prostate (Roosen et al, 2009), indicating a possible synergism. It has been shown that there are functional muscarinic receptors mediating contraction in vasa deferentia taken from the mouse (Cuprian et al, 2005) and guinea pig (Solanki et al, 2007), and we also observed that atropine attenuated contraction in vasa deferentia taken from wild-type mice. However, after purinergic and adrenergic blockade we did not observe a cholinergic residual response.…”
Section: Discussionsupporting
confidence: 74%
“…In mouse vas deferens, contraction and confocal studies have shown that nicotine increases the amplitude of the bretylium-resistant contraction (Cuprian et al 2005) and spontaneous Ca 2+ transients in all varicosities, located on either bretylium-sensitive or bretylium-resistant nerve terminals (Brain et al 2001; Jackson et al 2001; Jackson and Cunnane 2002). These nerve terminals were considered to be preterminal sympathetic fibres, sensory nerves or cholinergic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported a cholinergic component of contraction in the mouse vas deferens which is limited by the action of acetylcholinesterase (AChE), enhanced by nicotine and blocked by muscarinic acetylcholine receptor (mAChR) antagonists (Cuprian et al 2005). Nicotine acts at prejunctional nicotinic acetylcholine receptors (nAChRs) and therefore increases neurotransmitter release.…”
Section: Introductionmentioning
confidence: 99%
“…However, although a direct cholinergic innervation has been reported in murine vas deferens (Cuprian et al. 2005) it seems unlikely to account for the results of this study, for two main reasons. Firstly exogenous application of Cch failed to evoke a response in isolated VDSMC and secondly, we found that both prazosin and guanethidine inhibited the sustained phase of EFS-evoked contractions.…”
Section: Discussionmentioning
confidence: 74%